KINERJA PELAYANAN JALUR PEDESTRIAN DI PASAR ACEH MENGGUNAKAN METODE CUSTOMER SERVICE INDEX (CSI) - Cut Mutiawati; Fitrika Mita Suryani; Muhammad Isya; Ruhdi Faisal (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2021)
The pedestrians’ sidewalk is part of the transportation infrastructure in the city that has a role and function in providing service and convenience to the citizen. One of the cities that actively build pedestrian sidewalks is Banda Aceh. There were some problems in the sidewalk; the up and down sidewalk, slippery surface, high ramp, and many other obstacles. Thus, this research aimed to measure the pedestrians' satisfaction in three streets in Pasar Aceh, namely Chik Pante Kulu street,  K.H. Dahlan street, and Diponegoro street, by using the Customer Satisfaction Index (CSI). The analysis result indicated that most pedestrians’ sidewalk facilities need to prioritize their performance improvement. It was concluded from the sidewalk performance in the three streets evaluation. The dominant average value is "poor" and "moderate." Based on the gap value,  The five variables in Tgk. Chik Pante Kulu Street and the three variables in K.H. Dahlan Street were positive. However, it did not describe that the pedestrians’ sidewalk was good because the respondents considered the variable less important. Thus, the value of importance in the variable is lower than its performance value. The performance of the pedestrians’ sidewalks in the variable was "poor" and "moderate" (it did not include in the "good" category). The average index value of  Customer Satisfaction was 60% on the three pedestrians’ sidewalks, indicating that Customer Satisfaction was low and improvement was necessary for the future.